Neutrophil to lymphocyte ratio (NLR) in acute pancreatitis as an early predictor of severity and outcome - Bhanou, Noor Mohammed Shawnas; Balachandran, Gayatri; Jain, Nisha B. (International Surgery Journal, 2018)
Background: The management of Acute Pancreatitis (AP) is determined by an accurate assessment of severity of the disease. Numerous severity indicators have been described till date, most of which require reassessment after admission and resuscitation. We propose a novel indicator, the Neutrophil to Lymphocyte ratio (NLR), as a predictor of severity of acute pancreatitis at the initial time of diagnosis. NLR may have a role in predicting the length of hospital stay and ICU admission and also to predict adverse manifestations of Severe Acute Pancreatitis (SAP) including organ failure. Methods: A retrospective analysis was performed of 107 patients diagnosed with acute pancreatitis based on Atlanta 2012 definitions, who were admitted and treated between August 2017 and November 2017. The patients were grouped according to severity of acute pancreatitis and organ failure occurrence and a comparative analysis was performed to compare the NLR between groups. NLR was also compared with the modified Marshall score as a standard predictor of organ failure in acute pancreatitis. Results: Median NLR among the severe group is significantly higher compared to mild and moderate group (P <0.001). NLR significantly correlated with length of hospital stay (p 0.004) and also had a statistically significant correlation with ICU stay (p < 0.001). We found in our study that NLR at admission correlated significantly with the modified Marshall score in predicting the organ failure (p <0.001) in patients with acute pancreatitis. The receiver operator characteristic (ROC) curve analysis showed a cut-off values of NLR >8.5 at admission correlated with adverse outcomes in patients with acute pancreatitis. Conclusions: Neutrophil to Lymphocyte ratio (NLR) can be used as a predictor of severity of acute pancreatitis, right at the time of initial diagnosis. Further it may predict adverse outcomes, need for ICU care as well as length of hospital stay. NLR can be used as a tool to refer at risk patients to tertiary center needing ICU admission.